Pengaruh Beban Impak Jatuh Bebas Pada Produk Inovasi Parking Bumper Dari Bahan Polymeric Foam Diperkuat Serat Tandan Kosong Kelapa Sawit (TKKS) - Syukarni Ali (universitas teuku umar, 2015)
The use of waste oil palm empty Fruit bunches (OPEFB) is rapidly increasing.OPEFB Fiber are potential to be made engineering product especially innovative products. The innovative products can be used for technical component cases, especially products which have lifespan, durability, easily designed, recyclable, corrosion resistant, and heat absorbent as well as economical.The aims of this research was the effect of impact loads for innovative products manufacturing Parking Bumper polymeric foam material. The impact was tested by using free fall Impact testing device and Impact Test Specimens were done by using ASTM D1621-00.The result parking bumper design in simulation showed the stress value of 0.13 MPa. For trapezium type. which Force is provided for 4425 N, the dimension of the parking bumper 250 x 200 x 130 (mm). Simulations performed using Ansys workbench 12.1., the result of mechanical properties showed the second composition with the variation of the fall height was not close enough. This indicate that the second composition (Blowing Agent 15%, 70% Resin, Fiber 10%, Catalyst 5%) for parking bumper product would become more accurate and perfect.Keywords: waste (OPEFB), innovative products, parking bumper, free fall impact testing device